Critical torque, estimated time to exhaustion, and anaerobic work capacity from linear and nonlinear mathematical models - Hendrix, C. R.; Housh, T. J.; Mielke, M.; Zuniga, J. M.; Camic, C. L.; Johnson, G. O.; Schmidt, R. J. (Medicine & Science in Sports & Exercise, 2009)
Theoretically, critical torque (CT) is the maximal isometric torque that can be maintained without fatigue, and anaerobic work capacity (AWC) is the total "isometric work" associated with stored energy sources within the muscle.